Determinan yang Mempengaruhui Implemntasi Confrence Perawat di Ruang Rawat Inap Rumah Sakit - Naryati Naryati; Aisyah Aisyah; Siti Latipah; Giri Widakdo; Nuraenah Nuraenah (Universitas Malahayati Lampung, 2026)
ABSTRACT Pre-conference and post-conference activities are essential components of nursing care management because they facilitate coordination, care planning, evaluation, and the exchange of clinical information among nurses. Inadequate implementation of nursing conferences may increase the risk of communication errors, discontinuity of care, and threats to patient safety. Objective: This study aimed to analyze factors associated with the implementation of nursing conferences in the inpatient wards of Jakarta Islamic Hospital Cempaka Putih. Methods: This study employed a quantitative approach with a cross-sectional design. The study population and sample consisted of 122 inpatient nurses. Data were collected using a Likert-scale questionnaire measuring nurses’ attitudes, supervision, workload, management support, and conference implementation. Data were analyzed using univariate and bivariate analyses. Results: Most respondents were female (82%), held a professional nursing degree (73%), were classified as Clinical Nurse Level I (36.1%), and had worked for less than five years (50.8%). The majority of respondents demonstrated good conference implementation, accounting for 94 nurses (77%). Most nurses had poor attitudes toward conference implementation (61.5%) and perceived supervision as poor (69.7%). Most respondents had a moderate workload (59.8%) and received good management support (72.1%). Bivariate analysis showed that nurses’ attitudes, supervision, workload, and management support were significantly associated with nursing conference implementation (p 0.001). Conclusion: The implementation of nursing conferences is associated with both individual and organizational factors, particularly nurses’ attitudes, supervision, workload management, and management support. Hospitals should strengthen supervision, monitoring, workload arrangements, and compliance with pre-conference and post-conference procedures to improve nursing care coordination and patient safety. Keywords: Management Support, Nurse Attitude, Nursing Conference, Supervision, Workload. ABSTRAK Pre conference dan post conference merupakan bagian penting dalam manajemen asuhan keperawatan karena berfungsi sebagai sarana koordinasi, perencanaan, evaluasi, dan penyampaian informasi klinis antarperawat. Pelaksanaan conference yang tidak optimal dapat meningkatkan risiko kesalahan komunikasi, ketidaksinambungan asuhan, dan gangguan terhadap keselamatan pasien. Penelitian ini bertujuan menganalisis faktor-faktor yang berhubungan dengan implementasi conference perawat di ruang rawat inap Rumah Sakit Islam Jakarta Cempaka Putih. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Populasi sekaligus sampel penelitian berjumlah 122 perawat ruang rawat inap. Data dikumpulkan menggunakan kuesioner berskala Likert yang mengukur sikap, supervisi, beban kerja, dukungan manajemen, dan implementasi conference. Data dianalisis secara univariat dan bivariat. Hasil: Sebagian besar responden berjenis kelamin perempuan (82%), berpendidikan profesi Ners (73%), berada pada jenjang Perawat Klinik I (36,1%), serta memiliki masa kerja kurang dari lima tahun (50,8%). Implementasi conference mayoritas berada dalam kategori baik, yaitu sebanyak 94 perawat (77%). Mayoritas perawat memiliki sikap dalam kategori buruk (61,5%), supervisi buruk (69,7%), beban kerja sedang (59,8%), dan dukungan manajemen baik (72,1%). Hasil analisis bivariat menunjukkan bahwa sikap, supervisi, beban kerja, dan dukungan manajemen memiliki hubungan yang bermakna dengan implementasi conference perawat (p 0,001). Kesimpulan: Implementasi conference perawat dipengaruhi oleh faktor individual dan organisasi, terutama sikap perawat, pelaksanaan supervisi, pengelolaan beban kerja, dan dukungan manajemen. Rumah sakit perlu memperkuat supervisi, monitoring, pengaturan beban kerja, serta kepatuhan terhadap prosedur pre conference dan post conference untuk meningkatkan koordinasi asuhan dan keselamatan pasien. Kata Kunci: Beban Kerja, Conference Keperawatan, Dukungan Manajemen, Sikap Perawat, Supervise.